Analisis Rintisan Kewirausahaan di Sektor Minuman Tradisonal : Peluang dan Tantangan dalam Bisnis Teh Rempah - Eka Lestari; Munawaroh Munawaroh (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The spice tea business, as part of the traditional beverage sector, has great potential to be developed as a pioneering entrepreneurship amidst increasing public awareness of a healthy lifestyle and consumption of natural-based products. Opportunities and challenges faced in developing this spice tea business as a form of entrepreneurial innovation based on local traditions. The main opportunities for developing the spice tea business lie in the diversity of spices in Indonesia, market trends that support organic and herbal products, and the potential for export to the global market. In addition, the sustainability of this business can also be improved through flavor innovation, modern packaging, and digital marketing strategies. However, the main challenges faced include limited capital, fluctuations in raw material prices, competition with modern beverage products, and low digital literacy among business actors.